Crystal Structure and Chemical Bonding Properties of B Containing Ni-Fe Oxides Synthesized Under High Temperature Steam Conditions - Jung, Sang-Hyuk; Yeon, Jei-Won; Kang, Yong; Song, Kyuseok (Asian Journal of Chemistry, 2012)
Boron containing nickel iron mixed oxides were synthesized under a high temperature steam conditions. The mixed oxides were controlled with an Ni/Fe ratio at 1.5 and the boron content of 2 wt %. The crystal structure and the chemical bonding of the B containing Ni-Fe mixed oxides were measured as a function of temperature by an XRD and FT-IR spectrometer. The presence of B in the mixed oxides promoted the formation of a crystal structure and chemical bonding of NiFe2O4. Through the chemical bonding analysis, we confirmed that the chemical bonding of bonaccordite Ni2FeBO5 started forming at a temperature range of between 400 and 500 ºC.